Solvent Transport Properties of Er/Ps Thermoplastic Elastomeric Blends. Issue 1 (February 2015) - Vijayakumar, PC; Jeevan Kumar, R.; Johns, Anish; Sathyan, N; Johns, Jobish
Novel thermoplastic elastomeric blends from Polystyrene (PS) and Exudated Resin (ER) of Ailanthus Malabaricum tree are prepared by solution casting technique. The applicability of the resulting materials to design and fabricate barrier rubber materials for the transport and storage of liquids and gases has been studied in terms of solvent resistivity. It is important to carry out the transport studies to eliminate diffusion of chemicals into such material products. The sorption and diffusion of benzene through blends of Polystyrene and Exudated Resin of different compositions are studied at 35°C, 55°C and 65°C. The effects of blend ratio on diffusion, sorption and permeation coefficients are determined. The sorption data is used to estimate the activation energies of diffusion and permeation parameters. An anomalous behavior is observed for most of the blend compositions. The blend with 60/40 PS/ER combination at 35°C and 65°C exhibited Fickian transport mechanism. Minimum solvent uptake is observed for the blend ratio 60/40 PS/ER. This blend ratio shows better compatibility between the phases among the series of the blends studied.